Tinjauan Konsep Model Inovasi dalam Pengembangan Kurikulum Merdeka Sebagai Strategi yang Digunakan dalam Mengimplementasikan Kurikulum Baru Pada Konteks Pendidikan - Faridatun Nikmah (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2021)
This paper provides an overview of innovative models in curriculum development, focusing particularly on the implementation of the independent curriculum (Kurikulum Merdeka) as a strategy for introducing new curricula in the educational context. The study delves into the conceptual frameworks and methodologies underpinning curriculum innovation, examining how these models have been utilized to shape and enhance the educational landscape. By analyzing the strategies employed in implementing the Kurikulum Merdeka, the paper aims to elucidate the principles and practices driving curriculum reform efforts. Through this exploration, insights are gained into the challenges and opportunities associated with curriculum innovation, ultimately contributing to a deeper understanding of educational policy and practice in curriculum development.